Paradigma Pendidikan Islam Modern Dalam Perspektif Ontologis - musanna, syarifah; Rijal, Syamsul; M yunus, Firdaus (Institut Agama Islam Sumatera Barat Pariaman, 2025)
The problem of Islamic education is an urgent problem that needs to be emphasized in analyzing educational failures. Therefore, ontology becomes a means of discussing how the essence of education is implemented. The aim of this research is to determine the paradigm of modern Islamic education from an ontological perspective. This research method uses library research. The result of this study is that Islamic education cannot be separated from the divine dimension (revelation). All components contained in the education system will be extracted from divine revelation. In addition to the birth of certain terms in Islamic education, it can also be seen from several discussions on educational issues that refer to divine texts.